THE INTERNALISATION OF ANTI-CORRUPTION VALUES THROUGH CHARACTER EDUCATION IN HIGHER EDUCATION - Ega Nanda Putri Ayuana; Yusuf Adam Hilman (Jurnal Honai, 2026)
Corruption is a serious problem that impacts national development and public trust. Universities have a strategic role in instilling anti-corruption values ​​through character education that teaches honesty, integrity, responsibility, and academic ethics. This research used a literature review method, analyzing various national and international scientific journals published between 2023 and 2025. The results indicate that internalizing anti-corruption values ​​can be achieved through the integration of anti-corruption education courses into the curriculum, support from campus policies, exemplary lecturers, and active student involvement. A healthy academic culture is a crucial factor in fostering honest and responsible behavior. The use of digital technology can also increase the effectiveness of anti-corruption learning. The implementation of this strategy is expected to produce a generation of students with integrity who are ready to become agents of change in corruption prevention.